e^3x=7
=> 3x =ln 7
=>x=ln7/3
=>x=.6486
2007-05-16 03:29:36
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
Okey dokey. To solve this, first divide by 2, yielding:
e^3x=7
Then proceed to take the natural log (ln) of each side, giving:
ln e^3x=ln7
Then, the rules of ln of e to a power, gives the power, equal to ln 7:
3x=ln7
x=ln7/3
sorry i don't have a calculator on me, but that'll do it
2007-05-16 10:28:23
·
answer #2
·
answered by homosapien15 2
·
0⤊
0⤋
2e^3x=14
e^3x=7
ln(e^3x) = ln7
3x = ln7
x = (1/3)ln7
x=1/3*1.94591015
x=0.648636717
2007-05-16 10:43:56
·
answer #3
·
answered by xcess v 1
·
0⤊
0⤋
2e^3x=14
e^3x=7 [divide both sides by 2]
ln(e^3x) = ln7 [use ln on both sides]
3x = ln7 [ln and e cancel out]
x = (1/3)ln7 [divide both sides by 3]
2007-05-16 10:27:18
·
answer #4
·
answered by Crystal 3
·
2⤊
0⤋
2e^3x=14
e^3x=7
3x = ln(7)
x = 1.946/3
x = .648
2007-05-16 10:28:43
·
answer #5
·
answered by jordanhendon 2
·
1⤊
0⤋
e^3x=7
3xlne=ln7
3x=ln7
x=(ln7)/3= .6486367
2007-05-16 10:36:29
·
answer #6
·
answered by rwbblb46 4
·
0⤊
0⤋
e^(3x) = 7
3x ln e = ln 7
x = ln 7 / 3
x = 0.649
2007-05-16 18:03:56
·
answer #7
·
answered by Como 7
·
0⤊
0⤋